Accelerating Renewable Energy Integration in Energy Planning Considering the PV Techno-Economics and Hourly Profile, Case Study: Indonesian Power Sector - Muthahhari, Ahmad Adhiim; Nugraha, Candra Febri; Fauzan, Naufal Hilmi; Subekti, Lukman; Budi, Rizki Firmansyah Setya (International Journal of Energy Economics and Policy, 2024)
In planning for the generation capacity expansion planning, it is crucial to consider the economics of scale and the availability of primary energy sources. Solar power generation or PV PP is a plant that is very dependent on the availability of solar irradiance and land. To achieve Net Zero Emission by 2060, the Indonesian government aims to increase PV capacity to 4.68 GW. To support the accelerated integration of PV power plants into the electrical system and fulfill economic and sustainable aspects, the ideal capacity of PV power plants needs to be considered. This study involves optimization and comparison with various scenarios to determine the optimal combination for PV power plant planning. In the optimization process, Mixed Integer Linear Programming (MILP) is used, assuming a load of 100 MW and various PV profiles. Based on the optimization results, to meet a 100 MW load, 138 MW of PV power plants are required, with a configuration of 125 MW for large-scale PV PP, 10 MW for medium-scale PV PP, and 3 MW for rooftop PV PP. The total cost needed is 11,445 thousand dollars, with an levelized cost of electricity (LCOE) of 4.75 c/kWh. This value is significantly lower compared to other scenarios. To supply for 24 h, PV PP can utilize BESS, with an LCOE reaching 7.79 c/kWh when optimal capacity and generation are achieved. The recommendation for determining the capacity of PV PP is to use the large-scale capacity scheme, both for daytime supply systems and for the 24-h scheme.